(untitled) (Journal of the College of Basic Education, 2024)
Perhaps the great status of the discipliner, teacher, or sheikh, that he was chosen to teach and discipline the children of the caliphs so that they would be role models for the common people to follow, had a great impact on the scholars’ competition to reach this high status. Perhaps what was said about the teacher is to demonstrate the greatness of his status, as he said (may God’s prayers and peace be upon him and his family) “But I sent a teacher. And it was said about him (the right of a teacher is greater than the right of parents, for the parent is the reason for present existence and mortal life, and the teacher is the reason for everlasting life.” All of this had a great impact on our choosing to study the personality of the scholar Al-Baghdadi Ibn Tabarzh, who graduated. In seeking knowledge from a teacher to boys in one of the Baghdad stores until he became a scholar who was referred to in Lebanon and given scientific titles such as Musnad al-Shamiyyin, Sheikh of Hadith... and others, and travelers began to flock to him from all sides.